Bad News for Refugees - Philo, Greg (Pluto Press, 2013)
Bad News for Refugees analyses the political, economic and environmental contexts of migration and looks specifically at how refugees and asylum seekers have been stigmatised in political rhetoric and in media coverage.Through forensic research it shows how hysterical and inaccurate media accounts act to legitimise political action which can have terrible consequences both on the lives of refugees and also on established migrant communities.Based on new research by the renowned Glasgow Media Group, Bad News for Refugees is essential reading for those concerned with the negative effects of media on public understanding and for the safety of vulnerable groups and communities in our society.